(Technical Testing of Rotary Dryer for Cat's Whiskers Leaf (Orthosiphon stamineus benth)Leaf - H Guring Pohan; Endah Djubaedah; Noerdin N.K (Balai Besar Industri Agro, 1999)
Technical testing of rotary dryer was conducted to dry Cat's whiskers leaf (Orthorsiphon stamineus benth) the aim of the technical testing is to evaluate of performance the rotary dryer for drying cat's whiskers leaf. the drying temperature suitable for cat's whiskers leaf was 50-60 C. the result showed that the dryer reduce moisture from 72.47 % to 9.95% with drying rate 22.5% per-hours. The capacity of dryer is 2000 grams a batch and the heat efficiency was 14.05%.